Inertia is directly proportional to mass.
What is Walter Lewin famous for?
Walter Hendrik Gustav Lewin (born January 29, 1936) is a Dutch astrophysicist and former professor of physics at the Massachusetts Institute of Technology.
Lewin earned his doctorate in nuclear physics in 1965 at the Delft University of Technology and was a member of MIT's physics faculty for 43 years beginning in 1966 until his retirement in 2009.
According to Walter Levin,
The concept of moment of inertia is demonstrated by rolling a series of cylinders down an inclined plane.
Inertia is the resistance of any physical object to a change in its velocity. This includes changes to the object's speed, or direction of motion. An aspect of this property is the tendency of objects to keep moving in a straight line at a constant speed when no forces act upon them.
By rolling a series of cylinders down on an inclined plane , he demonstrated that a cylinder have a smooth friction.
He compares the rolling cylinder by using hollow cylinder and a heavy cylinder , and finalize the result that a hollow cylinder moves slowly but the heavy cylinder move faster.
Hence , By doing this experiment he explained about the inertia that Inertia depend on the mass of the object. As the heavy the object it will take more time to travel or move.
Learn more about inertia here:brainly.com/question/3268780
#SPJ1
Answer:
about 2.7liters for women and 3.7liters for men
Explanation:
Answer:
![T=51.64^\circ F](https://tex.z-dn.net/?f=T%3D51.64%5E%5Ccirc%20F)
![t=180.10s](https://tex.z-dn.net/?f=t%3D180.10s)
Explanation:
The Newton's law in this case is:
![T(t)=T_m+Ce^{kt}](https://tex.z-dn.net/?f=T%28t%29%3DT_m%2BCe%5E%7Bkt%7D)
Here,
is the air temperture, C and k are constants.
We have
in
So:
![T(0)=70^\circ F\\T(0)=10^\circ F+Ce^{k(0)}\\70^\circ F=10^\circ F+C\\C=70^\circ F-10^\circ F=60^\circ F](https://tex.z-dn.net/?f=T%280%29%3D70%5E%5Ccirc%20F%5C%5CT%280%29%3D10%5E%5Ccirc%20F%2BCe%5E%7Bk%280%29%7D%5C%5C70%5E%5Ccirc%20F%3D10%5E%5Ccirc%20F%2BC%5C%5CC%3D70%5E%5Ccirc%20F-10%5E%5Ccirc%20F%3D60%5E%5Ccirc%20F)
And we have
in
, So:
![T(30)=60^\circ F\\T(30)=10^\circ F+(60^\circ F)e^{k(30)}\\60^\circ F=10^\circ F+(60^\circ F)e^{k(30)}\\50^\circ F=(60^\circ F)e^{k(30)}\\e^{k(30)}=\frac{50^\circ F}{60^\circ F}\\(30)k=ln(\frac{50}{60})\\k=\frac{ln(\frac{50}{60})}{30}=-0.0061](https://tex.z-dn.net/?f=T%2830%29%3D60%5E%5Ccirc%20F%5C%5CT%2830%29%3D10%5E%5Ccirc%20F%2B%2860%5E%5Ccirc%20F%29e%5E%7Bk%2830%29%7D%5C%5C60%5E%5Ccirc%20F%3D10%5E%5Ccirc%20F%2B%2860%5E%5Ccirc%20F%29e%5E%7Bk%2830%29%7D%5C%5C50%5E%5Ccirc%20F%3D%2860%5E%5Ccirc%20F%29e%5E%7Bk%2830%29%7D%5C%5Ce%5E%7Bk%2830%29%7D%3D%5Cfrac%7B50%5E%5Ccirc%20F%7D%7B60%5E%5Ccirc%20F%7D%5C%5C%2830%29k%3Dln%28%5Cfrac%7B50%7D%7B60%7D%29%5C%5Ck%3D%5Cfrac%7Bln%28%5Cfrac%7B50%7D%7B60%7D%29%7D%7B30%7D%3D-0.0061)
Now, we have:
![T=10^\circ F+(60^\circ F)e^{-0.0061t}(1)](https://tex.z-dn.net/?f=T%3D10%5E%5Ccirc%20F%2B%2860%5E%5Ccirc%20F%29e%5E%7B-0.0061t%7D%281%29)
Applying (1) for
:
![T=10^\circ F+(60^\circ F)e^{-0.0061*60}\\T=10^\circ F+(60^\circ F)0.694\\T=10^\circ F+41.64^\circ F\\T=51.64^\circ F](https://tex.z-dn.net/?f=T%3D10%5E%5Ccirc%20F%2B%2860%5E%5Ccirc%20F%29e%5E%7B-0.0061%2A60%7D%5C%5CT%3D10%5E%5Ccirc%20F%2B%2860%5E%5Ccirc%20F%290.694%5C%5CT%3D10%5E%5Ccirc%20F%2B41.64%5E%5Ccirc%20F%5C%5CT%3D51.64%5E%5Ccirc%20F)
Applying (1) for
:
![30^\circ F=10^\circ F+(60^\circ F)e^{-0.0061t}\\30^\circ F-10^\circ F=(60^\circ F)e^{-0.0061t}\\-0.0061t=ln(\frac{20}{60})\\t=\frac{ln(\frac{20}{60})}{-0.0061}=180.10s](https://tex.z-dn.net/?f=30%5E%5Ccirc%20F%3D10%5E%5Ccirc%20F%2B%2860%5E%5Ccirc%20F%29e%5E%7B-0.0061t%7D%5C%5C30%5E%5Ccirc%20F-10%5E%5Ccirc%20F%3D%2860%5E%5Ccirc%20F%29e%5E%7B-0.0061t%7D%5C%5C-0.0061t%3Dln%28%5Cfrac%7B20%7D%7B60%7D%29%5C%5Ct%3D%5Cfrac%7Bln%28%5Cfrac%7B20%7D%7B60%7D%29%7D%7B-0.0061%7D%3D180.10s)
Answer:
3 seconds
Explanation:
Applying,
Applying,
v = u±gt................ Equation 1
Where v = final velocity, u = initial velocity, t = time, g = acceleration due to gravity.
From the question,
Given: v = 0 m/s ( at the maximum height), u = 30 m/s
Constant: g = -10 m/s
Substitute these values into equation 1
0 = 30-10t
10t = 30
t = 30/10
t = 3 seconds